A Human Traffcikking: Konsep Riqab Sebagai Objek Distribusi Zakat Kajian Fikih & Ekonomi Kontemporer - Matnin, Matnin; Bari, Abdul (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
The purpose of this research is to try to reveal human trafficking as a crime against humanity, so that human trafficking includes eight groups of asnaf, namely riqab, who are entitled to receive zakat. For that, the contextual understanding of riqab in the current context should no longer be contextualized as slaves, but riqab must be understood in context, that is, those who are exploited economically and their honor. The writing method used is a qualitative approach. While the method used is conceptual analysis and search for relevant reference sources, such as the use of journals, books, theses, articles, journals, etc. The analysis used is a descriptive analysis that provides an explanation of the analysis and synchronizes it with the existing documents. The conclusion of this research is that human trafficking is classified as riqab (slavery), because there is a common evil. Therefore, human trafficking is included in the eight groups of asnaf who are entitled to receive zakat. Therefore, it is necessary for zakat regulators and the government to understand riqab in the context of being a victim of exploitation so that it has an impact on zakat management so that it can alleviate poverty and prevent poverty.